Reader Worlds: Constructing Context for Historical Readers of Pulp Fiction with Google Earth - Gruner, Marion (Imaginations)

(untitled) (York University, 2023)
In the late 19th and early 20th centuries, reading as a cultural practice was deeply woven into daily life and informed critical aspects of society. However, scholars often lament the lack of evidence available to reconstruct historical audiences of popular culture, and thus to understand how these texts shaped readers, and ultimately, the broader ideologies of the time. Reader Worlds is a research-creation project which examines how locative media can fill this gap. Converging the embodied storytelling capacities of locative media and the evocative letters published in the reader departments of the pulp Western Story Magazine during the 1920s, this paper and its corresponding virtual tour explore how immersive technologies offer layered meaning to the narratives of historical readers.